2009
DOI: 10.1124/mol.108.052563
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Phenelzine Alters Differentiation of Cultured Human and Mouse Preadipocytes

Abstract: Change in body weight is a frequent side effect of antidepressants and is considered to be mediated by central effects on food intake and energy expenditure. The antidepressant phenelzine (Nardil) potently inhibits both monoamine oxidase and semicarbazide-sensitive amine oxidase activities, two enzymes that are highly expressed in adipose tissue, raising the possibility that it could directly alter adipocyte biology. Treatment with this compound is rather associated with weight gain. The aim of this work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Whether the decrease in SSAO expression was a consequence of fat cell size reduction appears unlikely since the shrinking of lipid stores observed during prolonged fasting is not accompanied by a reduction of SSAO activity in adipose depots [28]. On the opposite, agents known to inhibit SSAO have been observed to limit lipogenesis in vitro [20]. On the basis of these previous observations, it can be proposed that inhibition of lipogenic effects of endogenous/dietary SSAO substrates participates to the limitation of fat deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the decrease in SSAO expression was a consequence of fat cell size reduction appears unlikely since the shrinking of lipid stores observed during prolonged fasting is not accompanied by a reduction of SSAO activity in adipose depots [28]. On the opposite, agents known to inhibit SSAO have been observed to limit lipogenesis in vitro [20]. On the basis of these previous observations, it can be proposed that inhibition of lipogenic effects of endogenous/dietary SSAO substrates participates to the limitation of fat deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, benzylamine [17], methylamine [18], or other SSAO substrates [19], activate adipocyte differentiation in several preadipocyte lineages and therefore partly reproduce the adipogenic action of insulin. Lastly, in vitro experiments showed that the hydrazine derivative phenelzine (which inhibits SSAO) alters the adipocyte differentiation of cultured human and mouse preadipocytes [20]. We therefore hypothesized that endogenous or dietary amines may reproduce in vivo such anabolic insulin-like effects, and if the amines can reach WAT, any sustained pharmacological inhibition of their oxidation could hamper fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…That may be a mechanism by which it causes weight gain. 115 The potent ability of PLZ to sequester toxic aldehydes may contribute to neuroprotective actions. 116 A PLZ metabolite produced by MAO has been proposed as the cause of GABA and alanine elevation 37 and increased brain ornithine, 117 but PLP deficiency may also be implicated.…”
Section: Differences Between Tcp and Phenelzinementioning
confidence: 99%
“…For T37i differentiation experiments, confluent cells were cultured in DMEM/Ham's F12, 10% FCS, 2 nM triiodothyronine (T3) and 20 nM insulin. Primary cultures of human subcutaneous preadipocytes were performed as previously described (Chiche et al, 2009). CBZ (Sigma Aldrich, Saint Quentin Fallavier, France) was dissolved in ethanol.…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…[ 3 H]-deoxyglucose ([ 3 H]-DOG) uptake and lipolysis were determined in mature adipocytes as previously mentioned (Chiche et al, 2009).…”
Section: Morphological and Biochemical Determinationsmentioning
confidence: 99%